Determination of Vitamin D Status in a Population of Ecuadorian Subjects - G. Maldonado; C. Paredes; R. Guerrero; C. Ríos (The Scientific World Journal)
Introduction. Vitamin D is a preprohormone known to play a key role in phosphocalcic metabolism; its main source comes from the synthesis at the skin level by ultraviolet (UV) radiation. Objective. The purpose of this study was to determine the levels of vitamin D in an Ecuadorian population. Materials and Methods. Retrospective study of Ecuadorian subjects from the city of Guayaquil, who had an initial study of 25 (OH)-D serum, as the indicator of Vitamin D status, in the period of 2015-2016. Results. A total of 269 Ecuadorian subjects were analyzed, with a mean age of 54.73 ± 16.58; 85% (229) were females and 15% (41) males; mean vitamin D was 27.29 ± 10.12 ng/dl [6.41–88.74]; 70% of the population showed levels below 30 ng/dL of vitamin D, whereas only 30% (81) had normal values. 69% (185) had levels between 29 and 10 ng/dl and 1% (3) levels below 10 ng/dl. High levels of vitamin D were evidenced in the summer months in relation to the winter months. Conclusion. It is evident that, despite the location of Ecuador and the intensity of UV rays it receives throughout the year, Ecuadorian subjects have insufficient levels of vitamin D.